Reichsparteitag-Nürnberg Ansichtskarte Nürnberger Burg SS Hakenkreuz... - Auteur inconnu (Wikimedia Commons, 1936)
Carte postale ancienne issue de Wikimedia Commons. Titre: Reichsparteitag-Nürnberg Ansichtskarte Nürnberger Burg SS Hakenkreuz Fahnen Wappen Spielmannszug Paradetrommel NSDAP Propaganda Nazi Party Nuremberg Rally 1936 Postcard Photo-Hoffmann Munich 36-6 Uncredited artist No known copyright. " Nuremberg Rally " (Reichsparteitag-Nürnberg). Postcard showing a painting of uniformed SS musicians (marching drummers) parading with helmets and snare drums, Swastika flags, coat of arms of Nuremberg, Nuremberg Castle, etc. | No signature (uncredited artist) | published by Verlag Photo-Hoffmann, Munich, Nazi Germany, card no. 36/6 | Nazi Party (NSDAP) propaganda
Droits : Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; Château; Carte postale